Addressing widespread misidentifications of traditional medicinal mushrooms in Sanghuangporus (Basidiomycota) through ITS barcoding and designation of reference sequences - Shan Shen; Shi-Liang Liu; Ji-Hang Jiang; Li-Wei Zhou (IMA Fungus)
Abstract “Sanghuang” refers to a group of important traditionally-used medicinal mushrooms belonging to the genus Sanghuangporus. In practice, species of Sanghuangporus referred to in medicinal studies and industry are now differentiated mainly by a BLAST search of GenBank with the ITS barcoding region as a query. However, inappropriately labeled ITS sequences of “Sanghuang” in GenBank restrict accurate species identification and, to some extent, the utilization of these species as medicinal resources. We examined all available 271 ITS sequences related to “Sanghuang” in GenBank including 31 newly submitted sequences from this study. Of these sequences, more than half were mislabeled so we have now corrected the corresponding species names. The mislabeled sequences mainly came from strains utilized by non-taxonomists. Based on the analyses of ITS sequences submitted by taxonomists as well as morphological characters, we separate the newly described Sanghuangporus subbaumii from S. baumii and treat S. toxicodendri as a later synonym of S. quercicola. Fourteen species of Sanghuangporus are accepted, with intraspecific distances up to 1.30% (except in S. vaninii, S. weirianus and S. zonatus) and interspecific distances above 1.30% (except between S. alpinus and S. lonicerinus, and S. baumii and S. subbaumii). To stabilize the concept of these 14 species of Sanghuangporus, their taxonomic information and reliable ITS reference sequences are provided. Moreover, ten potential diagnostic sequences are provided for Hyperbranched Rolling Circle Amplification to rapidly confirm three common commercial species, viz. S. baumii, S. sanghuang, and S. vaninii. Our results provide a practical method for ITS barcoding-based species identification of Sanghuangporus and will promote medicinal studies and commercial development from taxonomically correct material.